Back Cover: Proton Conductivity of Naphthalene Sulfonate Formaldehyde Resin‐Doped Mesoporous Niobium and Tantalum Oxide Composites (ChemSusChem 2/2015). Issue 2 (8th January 2015) - Turley, Jonathan P.; Romer, Frederik; Trudeau, Michel L.; Dias, Marcos L.; Smith, Mark E.; Hanna, John V.; Antonelli, David M.
<x xml:space="preserve">Abstract</x> The Back Cover image shows the movement of protons along an enhanced proton‐conducting pathway fabricated inside a mesoporous transition‐metal oxide impregnated with naphthalene sulfonate formaldehyde resin. Ambient moisture and the sulfonate groups of the 4–6‐unit oligomers bind to the Lewis acidic walls of the mesostructure, creating a channel for enhanced proton conduction at the interface. As protons enter the pores, they hop along the proximal oxygen sites, giving rise to proton conductivity values surpassing those of the Nafion standard used in the study. More details can be found in the Full Paper by Turley et al. on page 301 (DOI: 10.1002/cssc.201402546).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>